AN ANALYSIS OF SPEECH ACTS USED BY THE ENGLISH TEACHERS IN THE CLASSROOM TEACHING AND LEARNING PROCESS AT SMA NEGERI 1 SERIRIT - ., Ni Made Dwi Darmetri; ., Prof. Dr.I Ketut Seken,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan jenis-jenis tindak tutur yang diucapkan oleh guru selama kegiatan belajar mengajar, bagaimana tindak tutur diwujudkan dalam komunikasi pengajaran, dan fungsi pedagogik dari tindak tutur. Subjek penelitian ini adalah dua orang guru SMA Negeri 1 Seririt. Penelitian ini merupakan penelitian kualitatif. Data dikumpulkan melalui observasi dan wawancara. Data dianalisis menggunakan Miles and Huberman analisis data interaktif. Temuan penelitian menunjukan bahwa guru hanya menggunakan empat tindak tutur berupa directives, commisives, representatives, dan expressives dalam proses belajar mengajar. Dari 134 ucapan, guru mengucapkan 65% directives, 5.2% commisives, 18.6% representatives, and 11.2% expressives. Ada tiga fungsi pedagogik dari tindak tutur guru, yaitu kontrol, organisasi, dan motivasi. Tindak tutur directives, declaratives, dan commisives berfungsi sebagai kontrol dan organisasi, tindak tutur representatives berfungsi sebagai kontrol dan evaluatif, tindak tutur expressives berfungsi untuk memotivasi. Kata Kunci : Fungsi pedagogik, proses belajar mengajar, tindak tutur This study was intended to describe and explain kinds of speech acts produced by the English teachers during teaching and learning process, how speech acts were realized in instructional communication, and pedagogical functions of speech acts. The subjects of the study were two English teachers in SMA Negeri 1 Seririt. This study was a qualitative study. The data were collected through observation and interview. The data were analyzed by using Miles and Huberman interactive data analysis. The findings show that there were only four types of speech acts performed by the teachers, namely representatives, directives, expressives, and commissives. From 134 utterances, the teachers produced 65% directives, 5.2% commisives, 18.6% representatives, and 11.2% expressives. There were three pedagogical functions of the teachers’ speech acts, namely control, organization, and motivation. Directives and commisives speech acts were functioned as control and organizational function, representatives speech acts were functioned as control and evaluative functions, expressives speech acts was functioned as motivational function.keyword : Pedagogical functions, speech acts, teaching and learning process